S945L-CFTR molecular dynamics, functional characterization and tezacaftor/ivacaftor efficacy in vivo and in vitro in matched pediatric patient-derived cell models - Allan, Katelin M.; Astore, Miro A.; Fawcett, Laura K.; Wong, Sharon L.; Chen, Po-Chia; Griffith, Renate; Jaffe, Adam; Kuyucak, Serdar; Waters, Shafagh A. (Frontiers in Pediatrics, 2022)
Cystic Fibrosis (CF) results from over 400 different disease-causing mutations in the CF Transmembrane Conductance Regulator (CFTR) gene. These CFTR mutations lead to numerous defects in CFTR protein function. A novel class of targeted therapies (CFTR modulators) have been developed that can restore defects in CFTR folding and gating. This study aimed to characterize the functional and structural defects of S945L-CFTR and interrogate the efficacy of modulators with two modes of action: gating potentiator (ivacaftor (IVA)) and folding corrector (tezacaftor (TEZ)). The response to these modulators in vitro in airway differentiated cell models created from a participant with S945L/G542X-CFTR was correlated with in vivo clinical outcomes of that participant at least 12 months pre and post modulator therapy. In this participants’ airway cell models, CFTR-mediated chloride transport was assessed via ion transport electrophysiology. Monotherapy with IVA or TEZ increased CFTR activity, albeit not reaching statistical significance. Combination therapy with TEZ/IVA significantly (p=0.02) increased CFTR activity 1.62-fold above baseline. Assessment of CFTR expression and maturation via western blot validated the presence of mature, fully glycosylated CFTR, which increased 4.1-fold in TEZ/IVA-treated cells. The in vitro S945L-CFTR response to modulator correlated with an improvement in in vivo lung function (ppFEV1) from 77.19 in the 12 months pre TEZ/IVA to 80.79 in the 12 months post TEZ/IVA. The slope of decline in ppFEV1 significantly (p=0.02) changed in the 24 months post TEZ/IVA, becoming positive. Furthermore, there was a significant improvement in clinical parameters and a fall in sweat chloride from 68 to 28 mmol/L. The mechanism of dysfunction of S945L-CFTR was elucidated by in silico molecular dynamics (MD) simulations. S945L-CFTR caused misfolding of transmembrane helix 8 and disruption of the R domain, a CFTR domain critical to channel gating. This study showed in vitro and in silico that S945L causes both folding and gating defects in CFTR and demonstrated in vitro and in vivo that TEZ/IVA is an efficacious modulator combination to address these defects. As such, we support the utility of patient-derived cell models and MD simulations in predicting and understanding the effect of modulators on CFTR function on an individualized basis.